A study on the operational performance of the Trans Padang bus Corridor VI (City center - Andalas University) - Adji, Bayu Martanto; Jonrinaldi, Jonrinaldi; Masrilayanti, Masrilayanti; Narny, Yenny; Andriani, Andriani; Handayani, Putri Bian; Putri, Amalia Yunia (Akademisi dan Saintis Indonesia (ASASI), 2024)
Trans Padang is an integrated highway bus system in Padang City that has operated since January 2014. Buses run every day from 06.00 WIB to 19.00 WIB. No literature has been cited. Trans Padang Corridor VI Bus serves the corridor Andalas University to the city center, and the route distance is ±13. 14 km. In this research, a study was carried out to determine whether the operations of the Trans Padang Corridor VI Bus were following the Decree of the Director General of Land Transportation No. SK.687/AJ.206/DRJD/2002. Six parameters were studied: load factor, headway, waiting time, travel time, stopping time at bus stops, bus speed, and bus fleets. Two methods were used to collect data: a dynamic and static survey. dynamic survey was carried out to record the departure and arrival times of buses at each bus stop, the number of passengers getting on and off, the distance traveled by the bus, the bus route, the bus stop, the bus travel time, and the bus stopping time. static survey is carried out to record the arrival and departure times of buses at certain stops. The study results show that only the waiting time parameters follow the technical instructions; the existing waiting time is 6.03, and in the technical instructions, the waiting time is set at 5-10 minutes.